Green and facile synthesis of porous carbon spheres from waste solution for high performance all-solid-state symmetric supercapacitors. (16th September 2021) - Wu, Yan; Cao, Jing-Pei; Yang, Zhi-Hui; Wei, Yu-Lei; Zhuang, Qi-Qi; Zhao, Xiao-Yan; Zhou, Zhi; Lu, Yao; Bai, Hong-Cun
Abstract: Porous carbon spheres materials display huge potential for energy storage, but their general synthesis need chemical activation agent with highly corrosive to create pores. In this work, a simple, environment-friendly and less time-demanding method is used to prepared porous carbon spheres using K2 FeO4 as activation agent and waste solution as the precursor. The K2 FeO4 employ in this work acts both as an activating agent and a catalyst. In addition, replacing KOH with K2 FeO4 does not only reduce the corrosion of equipment but also increases the content of oxygen. The optimized porous carbon spheres with high specific surface area, hierarchical pore structure and surface heteroatom can deliver a high specific capacitance of 260 F g −1 at 0.1 A g −1 and good cycling stability (90% retention after 15000 cycles at 5 A g −1 ). Furthermore, the all-solid-state symmetric supercapacitors fabricated based on as-prepared samples exhibit good electrochemical performance in the PVA/KOH electrolyte. This work offers a green route to convert waste solution into porous carbon spheres, which are promising candidate material for supercapacitors to energy storage. Highlights: K2 FeO4 is used as an activating agent and a catalyst during the activation process. Porous carbon spheres is prepared from waste solution. PCS-T-R based all-solid-state supercapacitors possess good electrochemical properties.